Bridge superstructure - Rajagopalan, N. (Alpha Science International Ltd., 2006)
This book fulfils the above requirements for varous types of bridge decks normally used for short and medium spans. The support for the bridge superstructure could be different depending on site conditions. These supports do play a major role in affecting the behavious of the structure hence the analysis and design.